Efektivitas Sistem Informasi Akuntansi, Kesesuaian Tugas, dan Pemanfaatan Teknologi Informasi pada Kinerja Pegawai - Udayana, Dian Savitri; Juliarsa, Gede (E-Jurnal Akuntansi; Vol 32 No 1 (2022)DO - 10.24843/EJA.2022.v32.i01.p19, 2022)
Performance is the level of success achieved by a person in carrying out tasks compared to work standards or criteria that have been determined and agreed in advance. The purpose of this research is to provide empirical evidence regarding the effect of the effectiveness of the application of accounting information systems, the suitability of tasks with information technology, and the use of information technology on the performance of cooperative employees. This research was conducted at the Independent Farmers' Cooperative, Gadungan Village, Tabanan. The number of samples used as many as 40 samples, with the method used is the saturated sampling technique. Data was collected by means of a questionnaire. The analysis technique used is multiple linear regression analysis technique. The results of the study found that the effectiveness of the application of accounting information systems, task suitability, and the use of information technology had a significant positive effect on the performance of the employees of the Tani Usaha Mandiri cooperative in Gadungan Village, Tabanan. Keywords :  The Effect of The Efectiveness Accounting Information System Implementation; Duty Suitability; Utilization of Information Technolog; The Employee Performance.